Dampak Nilai Tukar Mata Uang Terhadap Perdagangan Internasional - Mawardi, Kholid (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
As international trade activities are increased, there are more regulative practices which might be barriers to trade. One of such hindrances is exchange rate volatility that affects trade activities both directly and indirectly. Exchange rate volatility of currencies can affect the trade engagements and as well as the trade balance of a country. One of the implications of the study is that the impacts of monetary policy changes on trade activities can be noticed significantly in the long-term. While impacts on export levels are usually immediate, import levels are changed in long-run. The research analyzes the correlation between inflation and devaluation and clearly states their impacts on trade balance. The case study about devaluation of the currency of Azerbaijan elaborates the impacts of currency volatility on exports which is illustrated and analyzed in this research. Moreover, inflation and devaluation correlations and their impacts on import level of a country are studied through correlation and multiple regression analyses based on the data exported from OECD and World Bank. The results conclude that exchange rate volatility significantly impacts the trade balance in terms of imports and exports. Given the results, exchange rate is a non-trade barrier and affects foreign trade.